Identification of Loci Affecting Accumulation of Secondary Metabolites in Tomato Fruit of a Solanum lycopersicum × Solanum chmielewskii Introgression Line Population - Ballester, Ana-Rosa; Tikunov, Yury; Molthoff, Jos; Grandillo, Silvana; Viquez-Zamora, Marcela; de Vos, Ric; de Maagd, Ruud A.; van Heusden, Sjaak; Bovy, Arnaud G. (Frontiers in Plant Science, 2016)
Semi-polar metabolites such as flavonoids, phenolic acids and alkaloids are very important health-related compounds in tomato. As a first step to identify genes responsible for the synthesis of semi-polar metabolites, quantitative trait loci (QTLs) that influence the semi-polar metabolite content in red-ripe tomato fruit were identified, by characterizing fruits of a population of introgression lines (ILs) derived from a cross between the cultivated tomato Solanum lycopersicum and the wild species Solanum chmielewskii. By analyzing fruits of plants grown at two different locations, we were able to identify robust metabolite QTLs for changes in phenylpropanoid glycoconjugation on chromosome 9, for accumulation of flavonol glycosides on chromosome 5, and for alkaloids on chromosome 7. To further characterize the QTLs we used a combination of genome sequencing, transcriptomics and targeted metabolomics to identify candidate key genes underlying the observed metabolic variation.